Pengaruh Beberapa Media Tanam terhadap Pertumbuhan Tanaman Cabai Rawit (Capsicum frutescens L.) - Jelita Oktaviani; Dina Handayani; Nusyirwan Nusyirwan (Biocaster : Jurnal Kajian Biologi, 2026)
This study aims to analyze the effect of a combination of soil, cocopeat, and rice husk charcoal on the vegetative and generative growth of cayenne pepper (Capsicum frutescens L.). This study was conducted at the Greenhouse, Medan State University, used a Completely Randomized Design (CRD) consisting of four treatments and six replications. The data obtained were analyzed using ANOVA, followed by Duncan's test at a 5% confidence level. The results showed that the combination of planting media significantly affected the growth and production of cayenne pepper (Capsicum frutescens L.). The soil + rice husk charcoal (3:1) treatment consistently produced the highest average for all observation parameters, including plant height, number of leaves, flowering time, number of fruits per plant and fruit weight per plant. The superiority of this media is related to the properties of rice husk charcoal which is able to increase aeration, and the ability to retain water, so it can affect healthy root development and nutrient absorption, especially phosphorus (P) which is very important for fruit formation. Thus, the combination of soil and rice husk charcoal (3:1) is the most effective treatment for increasing the productivity of cayenne pepper (Capsicum frutescens L.).